2007
DOI: 10.1007/s00115-006-2098-7
|View full text |Cite
|
Sign up to set email alerts
|

Reliabilität und Validität des revidierten Beck-Depressionsinventars (BDI-II)

Abstract: The German BDI-II demonstrates good reliability and validity in clinical and nonclinical samples. It may now replace the older version of the BDI for assessing self-rated severity of depression and course of depressed symptoms under treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
369
1
25

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 760 publications
(440 citation statements)
references
References 19 publications
8
369
1
25
Order By: Relevance
“…Los resultados obtenidos con esta dimensión en otros estudios, ya sea utilizando el HEXACO-PI-R u otros instrumentos, son en general inconsistentes. Por ejemplo, en población no clínica alemana, los síntomas de depresión se asociaban signifi cativamente con todos los dominios del NEO -F ive Factor Inventory (NEO-FFI) excepto con el f actor de Apertura (Kühner et al, 2007). Sin embargo, en otros estudios se ha constatado que algunas f acetas de la dimensión predicen síntomas depresivos en población general (Car rillo, Rojo, Sánchez-Bernardos y Avia, 2001).…”
Section: Discussionunclassified
“…Los resultados obtenidos con esta dimensión en otros estudios, ya sea utilizando el HEXACO-PI-R u otros instrumentos, son en general inconsistentes. Por ejemplo, en población no clínica alemana, los síntomas de depresión se asociaban signifi cativamente con todos los dominios del NEO -F ive Factor Inventory (NEO-FFI) excepto con el f actor de Apertura (Kühner et al, 2007). Sin embargo, en otros estudios se ha constatado que algunas f acetas de la dimensión predicen síntomas depresivos en población general (Car rillo, Rojo, Sánchez-Bernardos y Avia, 2001).…”
Section: Discussionunclassified
“…Total scale scores range from 0 to 63, with a higher score indicating more depressive symptoms. The German version (Kühner et al, 2007) of the BDI-II has shown similar psychometric properties as the original version. Cronbach's alphas for the present study are reported in Table 1.…”
Section: Beck Depression Inventory-iimentioning
confidence: 90%
“…The BDI was developed for the assessment of depressive symptoms that correspond to the Diagnostic and Statistical Manual of Mental Disorders-IV (DSM-IV) criteria for major depressive disorder and measures a somatic and a cognitive-affective dimension of depression (Beck et al, 1996;Kuhner et al, 2007). The BDI assesses symptoms related to sadness, feelings of guilt, perceptions of self-worth, suicidal ideation, and changes in appetite and body weight, among other characteristics.…”
Section: Psychological Assessmentmentioning
confidence: 99%